(untitled) (Research, Society and Development, 2024)
Sleep is a phase of the sleep-wake cycle that is divided into two phases, non-REM (NREM) sleep and REM sleep. This phenomenon is related to the hormone cortisol, through a change in the timing of the phases that compose sleep, which, due to the steroid’s effect, causes a more spaced division of the phases, reducing fragmentation and providing a more favorable environment for stress. As the increase occurs, there is an alteration in the neuroendocrine axis, which leads to a massive release of cortisol into the bloodstream whose effects are chronic stress, obesity, depression of the immune system, and a decrease in sleep quality. In addition to these factors, it is understood that daily context and pre-sleep nocturnal habits influence the period, since cortisol levels affect how the progression of falling asleep occurs and morning hormone concentrations. Therefore, the present study aims, through a bibliographic review study, to bring to the scientific community the relationship between sleep, its phases, quality and circulating cortisol levels.